Arginase impairs hypoxic pulmonary vasoconstriction in murine endotoxemia - Petersen, Bodil; Busch, Cornelius; Schaack, Dominik; Lasitschka, Felix (Respiratory research, 2019)
Hypoxic pulmonary vasoconstriction (HPV) optimizes the match between ventilation and perfusion in the lung by reducing blood flow to poorly ventilated regions. Sepsis and endotoxemia impair HPV. We previously showed that nitric oxide synthase 2 (NOS2) is required, but not sufficient, for the effect of endotoxin on HPV. The aim of the current study was to identify additional factors that might contribute to the impairment of HPV during endotoxemia. Gene expression profiling was determined using pulmonary tissues from NOS2-deficient (NOS2−/−) and wild-type mice subjected to endotoxin or saline challenge (control). HPV was accessed as the percentage increase in left pulmonary vascular resistance (LPVR) in response to left main bronchus occlusion (LMBO) in wild-type mice. Among the 22,690 genes analyzed, endotoxin induced a greater than three-fold increase in 59 and 154 genes in the lungs of wild-type and NOS2−/− mice, respectively. Of all the genes induced by endotoxin in wild-type mice, arginase 1 (Arg1) showed the greatest increase (16.3-fold compared to saline treated wild-type mice). In contrast, endotoxin did not increase expression of Arg1 in NOS2−/− mice. There was no difference in the endotoxin-induced expression of Arg2 between wild-type and NOS2-deficient mice. We investigated the role of arginase in HPV by treating the mice with normal saline or the arginase inhibitor Nω-hydroxy-nor-L-arginine (norNOHA). In control mice (in the absence of endotoxin) treated with normal saline, HPV was intact as determined by profound LMBO-induced increase in LPVR (121 ± 22% from baseline). During endotoxemia and treatment with normal saline, HPV was impaired compared to normal saline treated control mice (33 ± 9% vs. 121 ± 22%, P < 0.05). HPV was restored in endotoxin-exposed mice after treatment with the arginase inhibitor norNOHA as shown by the comparison to endotoxemic mice treated with normal saline (113 ± 29% vs, 33 ± 9%, P < 0.05) and to control mice treated with normal saline (113 ± 29% vs, 121 ± 22%, P = 0.97). The results of this study suggest that endotoxemia induces Arg1 and that arginase contributes to the endotoxin-induced impairment of HPV in mice.
Gesehen am 22.08.2019